Physical and psychiatry diseases of aged people in Malaysia: an evaluation in Ampang, Selangor, Malaysia - Abdullah @ Chuah Hock Leng, Osman (Scholars Academic and Scientific Publisher, 2015)
Ageing is now not only a problem in developed countries but also in developing countries. Malaysia is no exception to this. The main objective of this paper is to identify the physical and mental and phychiatry problems of aged people in Malaysia and the demographic factors associated with those living in Ampang, an urban area near Kuala Lumpur, Malaysia. A random survey of every fifth member of the aged community above 69 years old were selected for sample survey from Ampang Public Hospital and an old folks’ home. The samples selected were interviewed using a pretested structured questionnaire which included the GDS-30, ECAQ and Barthel Index. Out of 300 elderly residents approached (not more than 7% of the total population), 240 agreed to participate in the study, giving a response rate of 80%. The mean age of the respondents was 70 years old +7 years with a median of 70 years. The chronic illness and functional dependence of the surveyed aged people in Ampang were 60% and 16%, respectively. Depression is associated with problems of no income, not enough income or unemployment (p<0.05) whereas cognitive impairment was significantly associated with age, gender, ethnicity, married status and level of education (p<0.05). Keywords: Aged people, Physical illness and mental illness, Ampang, Malaysia.